Identification and characterization of microsatellites from calafate (Berberis microphylla, Berberidaceae)1. (5th July 2013) - Varas, Benjamín; Castro, María H.; Rodriguez, Roberto; von Baer, Dietrich; Mardones, Claudia; Hinrichsen, Patricio
Abstract : Premise of the study: Southern barberry or calafate ( Berberis microphylla ) is a shrub species endemic to the Patagonian region of South America that is used for human consumption. The fruit is very rich in vitamin C and anthocyanins and has a very high antioxidant capacity. There have been only a few genetic studies of this and other closely related species. Methods and Results: Here we present the first 18 microsatellite markers of B. microphylla that were characterized using 66 accessions of calafate from Patagonia. On average, they had 7.6 alleles per marker, with an expected heterozygosity of 0.688. The informativeness of these markers was also evaluated in another 15 Berberis species, including most of the native and endemic Chilean species. Conclusions: The results confirm that these new simple sequence repeat markers are very polymorphic and potentially useful in genetic studies in any species of the genus Berberis .